ANIMAL METAPHOR AND SPECIESISM: RHETORIC OF POWER IN POST-MODERN CONTEXT - Copstein, Liège; Silva, Denise Almeida (Laboratório Editorial FCL-UNESP, 2014)
This article aims to contribute to the consolidation of an anti-speciesist critical perspective in the literary field, relating it to analytical approaches which include, within their object of analysis, sociological minorities within the postmodern and postcolonial context. To do so, we resort to Aristotle´s assumptions on rhetoric, Michel Foucault's formulations on discourse, the concepts of acractic and encratic doxas proposed by Roland Barthes, as well as the contribution of the philosophers Peter Singer and Gary Francione in the conceptualization of speciesism, which is further illustrated by J.M. Coetzee´s novel The lives of animals. The analogy between the discursive constructions that spread speciesism while encratic doxa and other forms of Cartesian-based exclusions, particularly those practiced in colonial circumstances, reinforces our conclusions about the legitimacy of the anti-speciest critic as a valid tool for understanding literature  and the sociocultural processes that it represents.